Review of PD-1/PD-L1 Inhibitors in Metastatic dMMR/MSI-H Colorectal Cancer - Oliveira, André F.; Bretes, Luís; Furtado, Irene (Frontiers in Oncology, 2019)
There are a wide range of therapies for metastatic colorectal cancer (CRC) available, but outcomes remain suboptimal. Learning the role of the immune system in cancer development and progression led to advances in the treatment over the last decade. While the field is rapidly evolving, PD-1 and PD-L1 inhibitors have a leading role amongst immunomodulatory agents. They act against pathways involved in adaptive immune suppression resulting in immune checkpoint blockade. Immunotherapy has been slow to impact the management of this patient population due to disappointing results, mainly when used broadly. Nevertheless, some patients with microsatellite-instability-high (MSI-H) or mismatch repair-deficient (dMMR) CRC appear to be susceptible to checkpoint inhibitors with objective and sustained clinical responses, providing a new therapeutic option for patients with advanced disease. This article provides a comprehensive review of the early and late phase trials with the updated data of PD-1/PD-L1 inhibitors alone or in combination with other therapies (immunotherapy, targeted therapy and chemotherapy). While data is still limited, many ongoing trials are underway, testing the efficacy of these agents in CRC. Current and future challenges of PD-1 and PD-L1 inhibitors are also discussed.